The Practicality of Popular Scientific Books based on the Diversity of Mangrove Shrubs in Tabanio Village - Chitania Millianton; Yudi Firmanul Arifin; Dharmono Dharmono (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
The development of a popular scientific book that is developed based on the local potential of a region is one solution that can be used to overcome problems that often arise such as a lack of student reading interest due to boring teaching materials and learning medifications in the Low Plant Botany course, especially in several studies of shrub diversity that require students to make direct observations. This development research aims to describe the practicality of the popular scientific book prototype entitled "Diversity of the Mangrove Shrubs in Tabanio Village." The research method used was the development model by EDR which was limited to the formative evaluation phase based on the Tessmer model. The results showed that the results of the feasibility test for popular scientific books got an average score of 88.9% with very good criteria and the results of student responses to popular scientific books got an average of 89.18% with criterion strongly agree. This shows that a popular scientific book entitled "Diversity of Mangrove Shrubs in Tabanio Village" is very practical to be used as an enrichment material in learning Low Plant Botany.AbstrakPengembangan sebuah buku ilmiah populer yang dikembangkan berdasarkan potensi lokal yang dimiliki sebuah daerah merupakan salah satu solusi yang dapat digunakan untuk mengatasi masalah-masalah yang sering muncul seperti kurangnya minat membaca mahasiswa karena bahan ajar dan medifikasi pembelajaran yang membosankan pada mata kuliah Botani Tumbuhan Tinggi khususnya pada beberapa kajian keanekaragaman semak yang mengharuskan mahasiswa untuk melakukan pengamatan langsung. Penelitian pengembangan ini bertujuan untuk mendeskripsikan kepraktisan prototipe buku ilmiah populer yang berjudul “Keanekaragaman Semak Mangrove Desa Tabanio” Metode penelitian yang digunakan ialah model pengembangan Education Design Reserch (EDR) yang dibatasi sampai pada fase evaluasi formatif berdasarkan model Tessmer. Hasil penelitian menunjukan hasil uji keterlaksanaan buku ilmiah populer mendapatkan nilai rata-rata 88,9% dengan kriteria sangat baik dan hasil respond mahasiswa terhadap buku ilmiah populer mendapatkan rata-rata 89,18% dengan kriteris sangat setuju. Hal tersebut menunjukan bahwa buku ilmiah populer dengan judul “Keanekaragaman Semak Mangrove Desa Tabanio” sangat praktis digunakan sebagai bahan pengayaan dalam pembelajaran Botani Tumbuhan Tinggi.